WORKSHOP UMKM MENDUNIA: CERDAS KEUANGAN, MELEK PAJAK DAN INVESTASI (PKM KKN UNS 271 DESA SUGIHAN, KECAMATAN TENGARAN, JAWA TENGAH) - Ary Setyawan; Risal Rayhan Farihat; Efazeta Fazafaza; Maharani, Sita Maharani; ⁠Arifin Irkham Wibawa; Muhammad Ilham Nur Fauzan; ⁠Rifqi Afifan; Annissa Latifaturrohmah; Miftahul Janah; Isna Aulia Adzani; Raditya Dwi Anggara (LPPM ITB AAS Indonesia Surakarta, 2025)
Abstract Micro, Small, and Medium Enterprises (MSMEs) have a significant contribution to the national economy, particularly in employment absorption and increasing Gross Domestic Product (GDP). However, low financial literacy, tax compliance, and investment understanding remain challenges for MSMEs, especially in rural areas. The “Global MSME Workshop: Financial Intelligence, Tax Literacy, and Investment” program implemented by the Sebelas Maret University 271 Community Service Program Team in Sugihan Village, Tengaran District, Semarang Regency, aims to improve understanding of financial management, strengthen tax literacy, and raise awareness of safe investments for MSMEs. The implementation method was carried out through a workshop with lectures, question and answer sessions, and interactive discussions. The results of the activity showed high enthusiasm from participants with the number of attendees exceeding the target, which was almost 100 people. Participants gained new insights regarding simple financial recording, MSME tax obligations, and wise investment planning. The active discussion also indicated an increase in public awareness and readiness to apply the material obtained. The conclusion is that workshop-based educational interventions have proven effective in contextually increasing the capacity of MSMEs and serving as a basic for strengthening a competitive, sustainable, and independent local economy. Keyword: Community Empowerment, Financial Literacy, Investment, MSMEs, Tax